2015
DOI: 10.5539/ies.v8n5p1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Visualization as Mediating between Mathematics Learning Strategy and Mathematics Achievement among 8th Grade Students

Abstract: Jordanian 8 th grade students revealed low achievement in mathematics through four periods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
3
11
0
1
Order By: Relevance
“…The former were found to score significantly better than the latter in both tests: making fewer mistakes, leaving fewer items blank, answering more items, and exhibiting a higher success rate per item answered. The present findings therefore corroborate the positive relationship between mathematical talent and visual ability reported earlier (Rivera, 2011;Ramírez-Uclés et al, 2013;Rabab'h and Veloo, 2015;Ramírez and Flores, 2017), for the CP students in the sample implemented efficient test strategies, answering rapidly and omitting very few items.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The former were found to score significantly better than the latter in both tests: making fewer mistakes, leaving fewer items blank, answering more items, and exhibiting a higher success rate per item answered. The present findings therefore corroborate the positive relationship between mathematical talent and visual ability reported earlier (Rivera, 2011;Ramírez-Uclés et al, 2013;Rabab'h and Veloo, 2015;Ramírez and Flores, 2017), for the CP students in the sample implemented efficient test strategies, answering rapidly and omitting very few items.…”
Section: Discussionsupporting
confidence: 91%
“…Traditional studies concluded that spatial awareness and the capacity to visualize abstract mathematical relationships were not necessarily components of mathematical talent (Krutetskii, 1976), whilst later studies revealed that talented students preferred non-visual methods (Presmeg, 1986). More recent research has found significant evidence of a relationship between visualization and mathematical ability, however (Rivera, 2011;Rabab'h and Veloo, 2015;Ramírez and Flores, 2017). The controversial findings are explained by the existence of different conceptions of mathematical talent and visualization, thereby requiring a clear view on what factors are used in the research to characterize both mathematical talent and visualization.…”
Section: Introductionmentioning
confidence: 99%
“…The visual component can play a key role in understanding the nature of the task and at the time of making conjectures, while the analytical component will be in the moment of generalization and justification of solutions. The degree of visualization used in solving a task depends on the visual or non-visual character of the task and also on the subject's particular cognitive styles that resolved the task, as has been emphasized by several studies (Godino, Blanco, Gonzato, Wilhelmi, 2013;Krutetskii, 1976;Pitta-Pantazi & Christou, 2009;Presmeg, 1986;Rabab'h & Veloo, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Traditionally, research has highlighted the low preference for visual methods by students with mathematical talent (Presmeg, 1986). However, more recent research has shown significant evidence for the relationship between visual perception ability and mathematical ability (Rabab'h & Veloo, 2015;Rivera, 2011). Reasoning in visual tasks requires the cognitive ability to work within a space that has no safe routines, and this characteristic hinders visualization (Arcavi, 2003).…”
Section: Theoretical Backgroundmentioning
confidence: 99%